Datathons across the globe: Potential for the development of (Open) Data Literacy - Eugenia Loría-Solano; Juliana Raffaghelli; Montse Guitert-Catasús (Firenze University Press, 2023)
This paper introduces a study aimed at understanding informal learning to develop open data literacy. Based on the open datasets and reports published by the Open Knowledge Foundation (OKF) on the globally organised event Open Data Day 2021, we extracted 20 records and applied to them quantitative and thematic analysis. Convergent and diversified patterns of engagement with the Open Data Day across the five continents were observed. On this basis, some formal and particularly, informal learning activities arise as a collaborative and participatory work of data communities seeking to work with open data. Along the several experiences there is concern about the technical skills to search, find and use Open Data, including data storytelling abilities. However, this set of abilities was not connected with a set of critical and holistic skills, required to promote some of the goals expressed by the ODDs. Overall, integrating formal and informal learning into a situated context should be considered to promote open data literacy.   Dathatons nel mondo: Potenziale per lo sviluppo di una alfabetizzazione ai dati (aperti). Questo documento introduce uno studio volto a comprendere l'apprendimento informale per sviluppare l'alfabetizzazione dei dati aperti. Sulla base dei set di dati aperti e dei rapporti pubblicati dalla Open Knowledge Foundation (OKF) sull'evento Open Data Day 2021 organizzato a livello globale, abbiamo estratto 20 record e applicato loro analisi quantitative e tematiche. Sono stati osservati modelli di impegno convergenti e diversificati con l'Open Data Day nei cinque continenti. Su queste basi, alcune attività di apprendimento formale e in particolare informale nascono come lavoro collaborativo e partecipativo delle comunità di dati che cercano di lavorare con i dati aperti. Lungo le diverse esperienze c'è preoccupazione per le capacità tecniche per cercare, trovare e utilizzare gli Open Data, comprese le capacità di data storytelling. Tuttavia, questo insieme di abilità non era connesso con un insieme di abilità critiche e olistiche, necessarie per promuovere alcuni degli obiettivi espressi dagli ODD. Nel complesso, l'integrazione dell'apprendimento formale e informale in un contesto situato dovrebbe essere presa in considerazione per promuovere l'alfabetizzazione dei dati aperti.